The Fourth Dimensions of the Job Demands-Resources (JD-R) Model of Work Engagement in Indonesian Context - Helmi, Avin Fadilla; Widhiarso, Wahyu; Marvianto, Ramadhan Dwi; Priwati, Acintya Ratna; Mustari, Muhammad Ahmad; Artikasari, Yasinta Vania (Jurnal Psikologi, 2020)
The purpose of this study was to evaluate the psychometric properties of the modified version of the Work Engagement Scale in the Indonesian context, by adding one aspect and test the effect of types of occupation using the multiple indicator multiple cause (MIMIC) model for testing measurement invariance. The sample of this study included 459 workers in Indonesia using 16 items of the Work Engagement Scale. The results revealed that Indonesian respondents have Asian characteristics, but they come from various ethnicities and cultures. By including university lecturers and industrial workers as respondents and performing confirmatory factor analysis followed by MIMIC model, it is discovered that Indonesian employees have satisfactory psychometric properties in all four dimensions, which comprise the constructs of the work engagement scale. The findings provide an insight into in the Job Demands-Resources (JD-R) Model of work engagement in Indonesian context consisted of vigor, dedication, absorption, and contribution dimensions from theoretical understanding. MIMIC model gives an evidence that the occupation types can affect the factor structure of work engagement, indicating that measurement invariance are not hold.